2016
DOI: 10.1371/journal.pone.0166941
|View full text |Cite
|
Sign up to set email alerts
|

How Effective Is Road Mitigation at Reducing Road-Kill? A Meta-Analysis

Abstract: Road traffic kills hundreds of millions of animals every year, posing a critical threat to the populations of many species. To address this problem there are more than forty types of road mitigation measures available that aim to reduce wildlife mortality on roads (road-kill). For road planners, deciding on what mitigation method to use has been problematic because there is little good information about the relative effectiveness of these measures in reducing road-kill, and the costs of these measures vary gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
195
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 242 publications
(234 citation statements)
references
References 28 publications
3
195
0
9
Order By: Relevance
“…An important next step is to perform applied studies in Asia, testing the effectiveness of different mitigation methods such as drift fences, culverts, bridges, or other wildlife passages (Patrick et al , Ascensão et al , D'Amico et al ). There are currently no such studies in Asia, but a meta‐analysis of the success of mitigation measures in other regions reported that fences are more effective than passages, and the combination of both is the most effective (Rytwinski et al ). Finally, citizen‐reported roadkill databases have been reported to be accurate for information on location and identification (Ha and Shilling , Waetjen and Shilling , Périquet et al ), and we recommend their further use in wildlife conservation and management.…”
Section: Discussionmentioning
confidence: 99%
“…An important next step is to perform applied studies in Asia, testing the effectiveness of different mitigation methods such as drift fences, culverts, bridges, or other wildlife passages (Patrick et al , Ascensão et al , D'Amico et al ). There are currently no such studies in Asia, but a meta‐analysis of the success of mitigation measures in other regions reported that fences are more effective than passages, and the combination of both is the most effective (Rytwinski et al ). Finally, citizen‐reported roadkill databases have been reported to be accurate for information on location and identification (Ha and Shilling , Waetjen and Shilling , Périquet et al ), and we recommend their further use in wildlife conservation and management.…”
Section: Discussionmentioning
confidence: 99%
“…Many projects involve implementing structures to keep wildlife away from roads (i.e., culverts, bridges; Rytwinski et al ). Roads are also fenced at places of frequent AVCs (Forman and Alexander ), audio and optical signal systems are installed to discourage animals from crossing roads (Rowden et al ), and speed limits, warning signals (Al‐Ghamdi and AlGadhi ), and thermal sensors draw the attention of drivers to the presence of large animals (Hirota et al ).…”
mentioning
confidence: 99%
“…). These are cheap and perhaps effective methods to reduce risks to wildlife, and may also make roads safer for (human) pedestrians (Drews , WHO , McLennan & Asiimwe , Rytwinski et al , Staton et al ).…”
Section: Discussionmentioning
confidence: 99%